Organic geochemistry of Mississippian shales (Bowland Shale Formation) in central Britain: Implications for depositional environment, source rock and gas shale potential. (January 2015) - Gross, D.; Sachsenhofer, R.F.; Bechtel, A.; Pytlak, L.; Rupprecht, B.; Wegerer, E.
Abstract: Marine Carboniferous shales are proven hydrocarbon source rocks in central Britain. In this contribution the depositional environment and shale gas/liquid potential of the lower Namurian part of the Bowland Shale Formation is studied using 77 thermally immature samples from the Duffield borehole. The Bowland Shale Formation comprises mudstone and turibidite lithofacies reflecting a pronounced sea level controlled cyclicity. The total organic carbon (TOC) content of the mudstones lithofacies (including marine bands) and of fine-grained rocks within the turibidite lithofacies varies between 1.3 and 9.1%. Hydrogen index (HI) values imply the presence of kerogen type III-II. According to biomarker ratios and bulk geochemical parameters, marine bands (maximum flooding surfaces, mfs) were deposited in deep water with slightly enhanced, normal, or slightly reduced salinity. Mudstones of the highstand systems tract (HST) were deposited in environments with normal to reduced salinity, whereas photic zone anoxia favoured the preservation of marine organic matter during deposition of the mfs and the HST. The supply of landplant debris increased during the HST. Turbidites and their non-calcareous mudstone equivalents represent lowstand systems tracts deposited in low salinity environments. Terrestrial organic matter dominates in turbiditic sediments, marine organisms prevail in time-equivalent mudstones. Mudstone beneath marine bands represents transgressive systems tracts when normal marine conditions and photic zone anoxia were re-established. The mudstone lithofacies exhibits a very good to excellent potential to generate conventional mixed oil and gas. TOC content of fine-grained rocks in the turbidite lithofacies depends on the amount of detrital minerals supplied from the south. Moreover, their organic matter is gas-prone. High TOC contents and large thicknesses of the mudstone lithofacies show that the Bowland Shale Formation holds a significant shale gas/liquid potential in areas with appropriate maturity. A relatively low average HI and high clay contents may have negative effects on the shale gas potential. Highlights: Reconstruction of the depositional environment of the Bowland Shale Formation. Bulk geochemical data and biomarker ratios reflect sea level controlled cyclicity. Bowland Shale Formation exhibits a very good to excellent oil/gas potential.